The significance of educational level in acquiring good literacy of COVID-19: a case study in Indonesia - Santi Martini; Kurnia D. Artanti; Sri Widati; Melyana Melyana; Firman S. Rahman; Chung-Yi Li (AOSIS, 2023)
Background: Surveys on Public Knowledge, Attitude, and Practice (PKAP) have been conducted in various countries with respondents from the public as well as health workers. Measuring the knowledge of the public about COVID-19 is very important to determine the knowledge gap among the public and also as an evaluation of the preventive efforts for COVID-19. Objective: The purpose of this research was to determine whether education level is a factor that affects one's literacy about COVID-19. Materials and Methods: This is cross-sectional research with online-based data collection using the Kobo toolbox application. The data collection was carried out from the 19th of April until the 2nd of May 2020. The number of people under study is 792. The level of knowledge was measured using 12 research questions with true or false question types. the multivariable logistic regression was carried out. Results: Most of the respondents (52.5%) were in the young age group (15-35 years old), were male (57.3%), and had a bachelor or diploma education level (62.1%). Furthermore, most of the respondents had good knowledge (65.4%). The higher the respondents' educational level means, the better knowledge they had concerning COVID-19 (P=0.013). Conclusions: Public knowledge about COVID-19 is affected by their level of education. A good level of knowledge about COVID-19 was found among respondents with master's and doctoral degrees. This finding can contribute to the prevention of COVID-19, in which the priority of educating communities about COVID-19 should be given to those having an educational level below a master's degree.